Pengetahuan dan Sikap tentang Perilaku Merokok pada Remaja - Julaecha Julaecha; Ajeng Galuh Wuryandari (Universitas Baiturrahim, 2021)
Smoking is a health problem in Indonesia and one of the main factors of several chronic diseases that can lead to death, although many smokers are aware and admit that smoking can lead to cancer. WHO estimates that the number of smokers in Indonesia in 2025 will increase to 90 million people, or 45% of the total population. Some adolescents think that smoking is a need to relax or other reasons that make smoking commonplace. The proportion of smoking among people aged ≥10 years in Indonesia with smoking behavior every day is 24.3% and occasional smoking is 4.6%. This study aims to determine the level of knowledge, attitudes and smoking behavior in adolescents. The research method used is correlational with cross sectional approach. The population in this study were students and female students at SMKN Kota Jambi, the sampling technique with accidental sampling was 49 people. The instrument used was a questionnaire. The collected data were analyzed by univariate and bivariate and statistical tests were performed using the ch-square test. The results showed that most of the respondents had good knowledge of 57.1%, a positive attitude of 59.1% and the majority of adolescents did not smoke 63.2%. The statistical test results showed no significant relationship between knowledge and smoking behavior (P> 0.005) but there was a significant relationship between attitude and smoking behavior in adolescents (P <0.005). It is hoped that the school will implement a smoking-free area and put up a warning poster for the dangers of smoking in the school environment and carry out continuous monitoring and evaluation